BES1 Functions as the Co-regulator of D53-like SMXLs to Inhibit BRC1 Expression in Strigolactone-Regulated Shoot Branching in Arabidopsis - Hu, Jie (Plant Commun, 2019)
Shoot branching, determining plant architecture and crop yield, is critically controlled by strigolactones (SLs). However, how SLs inhibit shoot branching after its perception by the receptor complex remains largely obscure. In this study, using the transcriptomic and genetic analyss as well as biochemical studies, we reveal the key role of BES1 in the SL-regulated shoot branching. We demonstrate that BES1 and D53-like SMXLs, the substrates of SL receptor complex D14–MAX2, interact with each other to inhibit BRC1 expression, which specifically triggers the SL-regulated transcriptional network in shoot branching. BES1 directly binds the BRC1 promoter and recruits SMXLs to inhibit BRC1 expression. Interestingly, despite being the shared component by SL and brassinosteroid (BR) signaling, BES1 gains signal specificity through different mechanisms in response to BR and SL signals.